A Family of Parallel and Interval Iterations for Finding All Roots of a Polynomial Simultaneously with Rapid Convergence (Journal of Computational Mathematics, 1984)
This paper suggests a family of parallel iterations with parameter p for finding all roots of a polynomial simultaneously. The convergence of the methods is of order p+2. The methods may also be applied to interval iterations.